Multilingual and Multimodal Repertoires as part of Identity Management on Facebook: A Case of International Students - Solmaz, Osman (Journal of International Students, 2018)
The present study examines the multilingual and multimodal repertoires of international graduate students on Facebook, displaying how semiotic and linguistic resources are employed to index multiple aspects of their identity in social media. Drawing on data from semistructured interviews and social media data of participants, this paper reveals that multilingual students frequently engage in linguistic and multimodal practices by mobilizing a great diversity of semiotic resources in their networks. The findings highlight that international students effectively use their repertoires to deal with a multitude of audiences and build identification performances signaling local and global affiliations. In this respect, the study contributes to the current thinking and investigation of identity management in social media through a mixed-methods approach including social network analysis.